Alphonsus de guimaraens, a poet of doubts: A reading of the sonnet “[crença e descrença! entre estes dois extremos]” - Amorim Braga, Gabriel (2023)
This essay focuses on the sonnet XXVI, “[Crença e descrença! Entre estes dois extremos]”, which is part of Pastoral aos Crentes do Amor e da Morte (1923), by Alphonsus de Guimaraens (July 24, 1870 – July 15, 1921), in order to suggest a reading of the poem that stands out because, between the religious lyricism and doubt, shines the duplicity of the Alphonsian core. Thus, there is, among other points, the goal of demonstrating, sometimes weaving considerations on the semantic content, sometimes analyzing the internal formal aspects, how the double is configured in the poetic invoice of the Brazilian symbolist.